Science Learning Game (SLG) Berbasis Augmented Reality untuk Meningkatkan Kemampuan Literasi Sains dan Berfikir Kritis Siswa Kelas VI SD - Mohamad Fatih; Cindya Alfi; Mohammad Afifuddin Muqtafa (Jurnal Penelitian Pendidikan IPA, 2024)
Science literacy is the ability of individuals to understand, evaluate, and apply scientific knowledge in everyday problem-solving, while critical thinking is the ability to analyze, evaluate, and make decisions based on evidence and logic. This research is based on several issues in SDN Sentul2 Kota Blitar in grade 6 post-Covid 19. This research aims to produce a product used as a learning tool in Grade 6, namely Science Learning Game (SLG) Media based on Augmented Reality to Improve Science Literacy and Critical Thinking Skills in Grade 6 Students in Kota Blitar. This research and development (R&D) study uses the ADDIE (analysis, design, development, implementation, and evaluation) model. The instrument used is a questionnaire. The research data analysis results show that the developed media can improve critical thinking skills, as evidenced by comparing the Pre-test results at 72.21% with the Post-test results at 93.57%. This media can also enhance science literacy, as indicated by the increase between the Pre-test results at 74.28% and the Post-test results at 92.14%. The implication is that the science literacy and critical thinking abilities of students in Indonesia still need improvement, which can be achieved by considering the use of instructional media. With positive results in pre-test and post-test scores, this media has the potential to enhance science literacy and critical thinking skills in students.